A pooled prevalence of fetal alcohol spectrum disorders in South Africa: a systematic review and meta-analysis protocol - Babatope O. Adebiyi; Ferdinand C. Mukumbang (BMC, 2021)
Abstract Background Fetal Alcohol Spectrum Disorder (FASD) remains a global public health problem. South Africa is estimated to have the highest recorded prevalence of FASD. However, no study has systematically evaluated the available prevalence studies to provide estimates that may facilitate effective planning and delivery of prevention and management services. Therefore, we propose to conduct a systematic review and meta-analysis to report a pooled estimate of the FASD prevalence among children, youth and adults in South Africa. Methods We will include quantitative (cohort and cross-sectional) studies that reported on the prevalence of FASD in South Africa. We will search databases such as Academic Search Complete, Education Resource Information Center (ERIC), SocINDEX, Health Source: Nursing/Academic Edition, Cumulative Index of Nursing and Allied Health and PsycARTICLES), Scopus, Science Direct, Springer Link, JSTOR, SAGE journals, PubMed, Web of Science and Sabinet. The references of included studies will be searched for additional studies on the prevalence of FASD. The search will be from inception to October 2021. Screening of (titles, abstracts and full text of the potentially relevant articles) will be done by two independent authors using software. All disagreements will be resolved by discussion. A standardised data extraction form will be designed for the extraction. Two authors will independently extract the data from the selected articles and all disagreements will be resolved by discussion. We will use a tool developed by Munn and colleagues to critically appraise all the included studies. The primary outcome will be the proportion of individuals with FASD in South Africa. We will use the Freeman-Tukey double arcsine transformation to transform the raw prevalence estimates so that the data can follow an approximately normal distribution. We will use random-effects models to calculate 95% confidence intervals and prediction intervals based on multiple meta-analyses with transformed proportions. We will test heterogeneity using Cochran's Q and describe using the I2 statistic. Discussion The pooled prevalence estimate will assist the government and other stakeholders (such as non-profit organisations and researchers) to plan and prioritise prevention and management interventions. Systematic review registration The protocol has been registered with PROSPERO (registration number: CRD42020197979 ).